From catastrophizing to catalyzing: does pain catastrophizing modulate the beneficial impact of open-label placebos for chronic low back pain? A secondary analysis - Elif Buse Caliskan; Elif Buse Caliskan; Katharina Schmidt; Andreas Hellmann; Tamás Spisák; Ulrike Bingel; Julian Kleine-Borgmann (Frontiers in Psychology)
Chronic back pain (CBP) is a global health problem with significant health and economic consequences. Traditional analgesics are often no better than placebo, highlighting the need for biopsychosocial approaches. Open-label placebos (OLPs), administered with patient consent, offer a promising alternative. Existing research has mainly focused on the effects of OLP treatments on patient-reported outcomes. In a previous randomized controlled trial (RCT), we investigated whether an OLP treatment improves subjective and objective outcomes such as spinal mobility in CBP patients. The analysis showed significant reductions in pain intensity, disability, and depressive symptoms after OLP combined with treatment-as-usual (TAU). However, objective improvements in spinal mobility were not observed. In this exploratory analysis, we aimed to identify predictors of objective improvement after OLP treatment. Psychological factors (e.g., depression, stress, and pain catastrophizing) and baseline physiological measures were analyzed using generalized linear models. Results showed that patients with lower pain catastrophizing exhibited increased spinal motion velocity in the OLP+TAU group, while those with higher pain catastrophizing did not. These findings suggest that OLP treatment may provide measurable benefits for a specific subset of patients, supporting its potential as a personalized intervention in managing CBP. Further research is needed to confirm these findings and to elucidate the role of psychological factors in chronic pain management.